Analysis of IPSec Implementation on Dynamic Multipoint VPN Protocol Using Routing Border Gateway Protocol - Muhammad Ali Said; Setyorini ‏‏‎ ‏‏‎ Setyorini‏‏‎; Erwid M Jadied (Forum Kerjasama Pendidikan Tinggi, 2022)
Dynamic Multipoint Virtual Private Network (DMVPN) technology is one of Cisco's solutions to overcome the limitations of VPN scalability. DMVPN has a combination of components: Next hop resolution protocol (NHRP), Multipoint Generic Routing Encapsulation (mGRE) and Routing protocol. This research implements a simple network consisting of Hub, Spoke1, Spoke2, Lan1, Lan2 and Lan3 using the GNS3 simulator. This study compares the performance of IPSec and without IPsec on DMVPN using the BGP Routing protocol on performance parameters namely delay, throughput, jitter and packet loss to evaluate the security impact of the DMVPN network. The results of this study indicate that IPSec DMVPN has an effect on sending UDP packets which have a throughput value without IPSec of 5082.18 kbit/s while IPSec's throughput is 5034.40 kbit/s. The value of packet loss without IPSec has a value of 7.54% while IPSec has a value of 4.79%. The results of the jitter value have the same value. The delay value without IPSec has a value of 0.183s while the IPSec delay value is 0.410s. TCP packet delivery has a throughput value without IPSec is 1139.16 kbit/s while the IPSec throughput value is 1105.20 kbit/s. The results of the packet loss value and the jitter value have the same value. The delay value without IPSec has a value of 0.185s while the IPSec delay value is 0.187s.